Study of Continuous and Intermittent Drying of Pear Through Mathematical and Diffusion Models - Lima, Leiliane Silva Lopes; Silva, Wilton Pereira da; Pereira, Joan Carlos Alves; Silva, Cleide Maria Diniz P. S. e (Journal of Agricultural Studies, 2022)
The methods for drying agricultural products are necessary to check the quality of the final product and feasibility of the process. The objective of this study was to perform the drying of pear by continuous and intermittent methods (α = 2/3) at two different temperatures, compare the two methods and describe the processes using mathematical and diffusion models to evaluate the saving of time and effective processing energy. For continuous drying, Page model was the one which best fitted to the experimental data, with highest coefficient of determination and lowest chi-square. Regarding intermittent drying Page model was also the one which best fitted to the experimental data for the two temperatures studied. When comparing the drying methods studied, it was found that intermittent drying produced a similar and considerably better effect on the energy saving aspect, compared with continuous drying: 41.7% at 50 °C and 25.8% at 70 °C. The effect of time intervals with the product out of the dryer, during the intermittent drying process, was reflected in the increase in the diffusion coefficient, so that the transport of moisture occurred more quickly for this type of drying, which contributes to justify the reduction of effective operating time and increased dry product quality.